Fragility, fluidity, and resilience: caregiving configurations three decades into AIDS. (25th July 2016) - Manderson, Lenore; Block, Ellen; Mkhwanazi, Nolwazi
ABSTRACT: HIV and AIDS have impacted on social relations in many ways, eroding personal networks, contributing to household poverty, and rupturing intimate relations. With the continuing transmission of HIV particularly in resource-poor settings, families and others must find new ways to care for those who are living with HIV, for those who are ill and need increased levels of personal and medical care, and for orphaned children. These needs occur concurrently with changes in family structure, as a direct result of HIV-related deaths but also due to industrialization, urbanization, and labor migration. In this special issue, the contributing authors draw on ethnographies from South Africa, Swaziland, Lesotho, Zambia, and – by way of contrast – China, to illustrate how people find new ways of constituting families, or of providing alternatives to families, in order to provide care and support to people infected with and afflicted by HIV.